"The Sorrows of Yamba," by Eaglesfield Smith and Hannah More: Authorship, Ideology, and the Fractures of Antislavery Discourse - Richardson, Alan (Romanticism on the Net)

(untitled) (Université de Montréal, 2002)
Abstract"The Sorrows of Yamba", published in 1795 by Hannah More in her Cheap Repository Tracts series, was one of the most popular and frequently reprinted antislavery poems of its time. Recently it has become popular once more, as a classroom text included (usually under More's name) in teaching anthologies, in anthologies of women's poetry, and in a selected edition of More's work. But the poem is not solely by Hannah More, who never signed it with her characteristic "Z." Following a stray reference by Wylie Sypher, I have located several versions of the poem signed by "E.S.J." and "Eaglesfield Smith." These versions are about half the length of the version in Cheap Repository Tracts: the material added (almost certainly by More) entirely change the tone and purpose of the poem, from a "slave suicide" poem to one that instead has the heroine converted by a passing missionary. More also adds a good deal of pseudo-dialect to the poem, making Yamba less tragic and dignified and more helpless and child-like. Recovering Smith's ur-version of the poem allows one to see two distinct strains of British anti-slavery discourse at work, one tragic and sentimental (and vaguely liberal), the other Christianizing and infantilizing (and distinctly reactionary). Far from underwriting a spurious unity as Foucault suggests in his critique of the individual author, concentrating on the authorship question in this instance reveals the ideological and formal discontinuities that critics have missed in this important antislavery poem.